Adubações orgânicas e manejo de adubo verde nos atributos químicos e biológicos do solo e na cultura da alface em sistema de cultivo orgânico - Oliveira, Luciana Cleci de (2009)
Due the lack of informatios about fertilization on lettuce (Lactuca sativa L.) in organic growth, this work aimed to study the effect of organic fertilizers on chemical and biological character of soil and on lettuce productivity. The green manure velvet bean (Mucuna aterrima) received two types of management: incorporation into the soil or not incorporation. These both areas received the solid organic fertilizer bovine manure, commercial organic fertilizer and organic compound and a control treatment without fertilization. The samples were obtained at the time of management of velvet bean, and at 15, 55 and 105 days after this process, representing the moments of the distribution of fertilizes, plant and harvest of lettuce, respectively. Were evaluated chemical and biological characteristics of soil, and agronomic characteristics of the lettuce cultivar Vanda. The results showed that the commercial organic fertilizer followed by the organic compound, provided that highest amorents of organic matter, P, K, Ca, Mg, CTC, pH and V, and the two types of management of velvet bean, incorporated or not has similar results. For microbial biomass, better results were fownd with velvet bean not incorporated into soil plus treatment with organic compound. The population of bacteria was increased in the area where velvet bean was incorporated, except for the treatment with organic compound. For fungi, not incorporated velvet bean associated with commercial organic fertilizer provided the higher rate of population. The incorporation of velvet bean associated with organic compound increased the population of mycorrhizal fungi. The bovine manure associated with the incorporation of velvet bean and treatment with organic compound without incorporation of velvet bean increased the population of saprophytic nematodes. The area of aerial part, number of leaves and total fresh and dry weights of aerial part of lettuce, higher values were observed without the incorporation of velvet bean associated with the use of commercial organic fertilizer or bovine manure treatmentes